(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
The Corporate University Model causes a lot of debate about whether this design will be more strategic in developing individual and organizational knowledge than traditional universities. Because of this, the researcher decided to conduct a study about the effectiveness of the aspects of the model to test its applicability in a fast-food restaurant. The study focused mainly on the TOPSPOT Multi-Purpose Cooperative’s training program regarding on-the-job training, Competency-Based Orientation, Curriculum, and Training Aids as assessed by selected rank-and-file and supervisory employees in the Philippines. It aimed to identify the correlation between the TOPSPOT Multi-Purpose Cooperative’s training program and KFC Philippines Competencies in Knowledge, Skills, and Abilities. This study used the descriptive method to gather the necessary information and assess the TOPSPOT Multi-Purpose Cooperative’s Training Program. A survey questionnaire was used across the Philippines to gather the needed data. The research covered all the employees who experienced the TOPSPOT Multi-Purpose Cooperative training program in the Philippines, which has 148 KFC branches. • Contingent on the assessment of the training program of Topspot Multi-Purpose Cooperative, the most effective indicator under the first aspect – On-the-Job Training is “The OJT experience enables mastery of the tasks needed to perform” and “The communication of the training program’s rules in the store’s standard operating procedure cultivates the learning.” For the Competency-Based Orientation, the top indicator is “The orientation communicates the competencies needed to trainees.” For the third aspect -Curriculum, the most effective indicator is “The training program is related to the job role in store.” For the fourth aspect – Training Aids, the most effective indicator is “The training materials and training room empower the training sessions to understand the lesson further.” Among the aspects, the respondents rated the Competency-Based Orientation as the most effective aspect of the training program. • Contingent on the respondents’ judgment of their competency, in terms of Knowledge, the most excellent indicator is “The training program communicates all the concepts and topics to the trainees.” Regarding Skills, the most excellent indicator is “The hands-on experience enables trainees to master tasks.” Regarding Ability, the most excellent indicator is “The training program encourages the trainees to commit to their job.” Among the aspects, the respondents assessed that Skills are the most excellent aspect of competency. • The On-the-Job Training, Competency-Based Orientation, Curriculum, and Training Aids had a consequential relationship with Knowledge, Skills, and Ability (KSA). • Knowledge, Skills, and Ability have no consequential divergence in terms of age, the number of seminars/trainings attended, and gender according to the assessment of the respondents. • Disseminate best practices to improve employee performance, increasing efficiency, profitability, and customer satisfaction. This concept can be applied operationally to effectively diagnose and address training and development needs. • Alignment of training with business needs is essential for long-term success. Organizations must adapt to their environment and evolve, mirroring the importance of employee development in corporate settings. • Corporate Universities focus on integrated training initiatives from a holistic education, encompassing technical skills, soft skills, and values. This approach is relevant in corporate settings, where trainees are expected to be dynamic. • Embracing new training methods and technology is critical for staying competitive and efficient, and the Corporate University welcomes this approach, which can significantly impact an organization’s ability to adapt to changing market dynamics. In corporations, staying up-to-date with the latest technologies and treatment methods is vital for satisfying their customers.